Kirk-Othmer Encyclopedia of Chemical Technology 2000
DOI: 10.1002/0471238961.0825040101220514.a01
|View full text |Cite
|
Sign up to set email alerts
|

Hydantoin and Its Derivatives

Abstract: Hydantoins are a group of closely related substances for which several general patterns regarding their physical properties, chemical reactivity, synthesis, and analysis can be found. Physical properties of hydantoin derivatives, including melting point and ionization properties, are discussed in terms of their relationship with molecular association through hydrogen bonds. A survey of their spectral properties (uv, ir, nmr, luminescence, and mass spectra) is also given. Treatment of chemical reactivity is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…The hydantoin (2,4-imidazolidinone) moiety is an important medicinal core unit . As can be seen from the structure, it can be derivatized at several positions.…”
Section: Introductionmentioning
confidence: 99%
“…The hydantoin (2,4-imidazolidinone) moiety is an important medicinal core unit . As can be seen from the structure, it can be derivatized at several positions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, according to the literature available, the hydantoins in aqueous solution can be hydrolyzed. In this process, in which ring-opening occurs to give the ureido acids as intermediate, which can hydrolyze to α-amino acids (Scheme 5), [62,63] , it was observed that the rate constant increase with increasing pH. [64][65][66][67][68] It suggests that the second process observed corresponds with the hydrolysis reaction of the 3-chlorohydantoin formed.…”
Section: Hydrolysis Of N-chloro-hydantoins Formedmentioning
confidence: 99%
“…The chemistry of hydantoins attracted a considerable attention because of their importance in medicine and industry [116117]. N-Nucleoside analogs with (thio)hydatantoin scaffold as a nucleobase mimic were also extensively investigated [118].…”
Section: Reviewmentioning
confidence: 99%